Circulating concentrations of 1,25-dihydroxyvitamin D3 in patients with primary hyperparathyroidism. - Thakker, R; Fraher, L; Adami, S; Karmali, R; O'Riordan, J (1986)
Vitamin D metabolism was studied in 65 patients with surgically proven primary hyperparathyroidism. The mean concentration of 1,25-dihydroxyvitamin D3 was 51.7 +/- 34 pg/ml (mean +/- SD) and was not significantly different from normal. Renal function was normal in 60 of these patients and in this group circulating 1,25-dihydroxyvitamin D3 was below the lower limit of normal in three and elevated in 17; it was related to the serum concentrations of amino-terminal parathyroid hormone, but was independent of serum calcium and the urinary excretion of calcium. The incidence of nephrolithiasis or hyperparathyroid bone disease or combined nephrolithiasis and bone disease in these patients was not related to the circulating concentration of 1,25-dihydroxyvitamin D3. In the remaining five patients, in whom renal impairment was present, circulating 1,25-dihydroxyvitamin D3 was below the lower limit of normal in four. Thus, in primary hyperparathyroidism the circulating concentration of 1,25-dihydroxyvitamin D3 is elevated in only a minority of patients and appears to be unrelated to the occurrence of nephrolithiasis or bone disease.